Bioaktivitas Antibakteri Ekstrak Spons (Porifera: Demospongiae) Dari Pulau Barrang Lompo dan Lae-Lae - Abdul Haris; Naharuddin Nabaing (Jurnal Ilmu Kelautan SPERMONDE, 2016)
Sponge is one group of marine organisms that potentially contain bioactive compounds. Bioactivities of compound extracted from sponge are influenced by the habitat where they live. To proof the effects of different habitat type on the sponge bioactivities,a study was conducted by examining sponge samples collected from Barrang Lompo and Lae-Lae Islands. Extraction was done using maseration method, while bioactivity was tested using agar diffusion method. Sponge species that collected from Barrang Lompo and Lae-lae islands were 40 and 23 species, respectively. In Barrang Lompo island, all extracts were active on Staphylococcus aureus and Vibrio cholerae, while in Lae-Lae Island, all extracts of sponge were active on Staphylococcus aureus but only 13 extracts were active on Vibrio cholerae. In term of fractional bioactivities, in Barrang Lompo Island, of 40 sponge species found, 26 fractions were active on Staphylococcus aureus and only 16 fractions that active on Vibrio cholerae. Bioactivities of extracts from Barrang Lompo Island were higher than those from Lae-Lae Island. Statistical analysis showedthat bioactivities of extracts taken from Barrang Lompo and Lae-Lae Island on Staphylococus aureus and Vibrio cholerae were significantly different. However, none differences detected on bioactivities among habitats.